Computational fluid dynamics modeling of liquid–gas flow patterns and hydraulics in the cross-corrugated channel of a plate heat exchanger. (January 2020) - Zhu, Xiaowei; Haglind, Fredrik
Highlights: CFD modeling of liquid–gas flows in a plate heat exchanger is reported for the first time. Bubbly flow, slug flow, churn flow and film flow in the cross-corrugated channel are successfully modeled and validated. The pressure drop and the void fraction of two-phase flows in the plate heat exchanger are quantified via CFD simulations. Correlations for the caculation of pressure drop and void fraction in the plate heat exchanger are developed. Abstract: The morphology of liquid–gas flows in corrugated plate heat exchangers is complex due to the intricate channel geometry. To date, only a few experimental visualizations have been performed to study the two-phase flow characteristics in plate heat exchangers. In this paper, we perform pioneering computational fluid dynamics simulations of the adiabatic liquid–gas (water-air) flow in a cross-corrugated channel of a plate heat exchanger. The standard volume-of-fluid technique is used to capture the complex phase-interfaces constructed by the cross-corrugated walls. In order to reduce the computational cost, the computational domain is simplified by a series of assumptions. The bubbly flow, slug flow, churn flow and film flow are modeled by varying the superficial velocities of both phases, and the validity of these patterns is proved by comparison with experimental results. A flow regime map is developed based on the numerical results, and the transitions between the regimes are discussed. The predicted pressure drop shows good agreement with the experimental data. The two-phase multiplier for general prediction of the friction factor in the cross-corrugated channel is calibrated. The mean void fraction in the channel is quantified by the numerical simulation. The void fraction model from Zuber and Findlay is found to be applicable to the cross-corrugated channel, which is further modified for general use for these types of channel flows.